Clinical application of comprehensive chromosomal screening at the blastocyst stage - Schoolcraft, W; Fragouli, E; Stevens, J; Munne, S; Katz-Jaffe, MG; Wells, D (2010)
Objective: To evaluate a new strategy for comprehensive chromosome screening at the blastocyst stage. Design: Clinical research study. Setting: An IVF clinic and a specialist preimplantation genetic diagnosis laboratory. Patient(s): Forty-five infertile couples participated in the study. The mean maternal age was 37.7 years, and most couples had at least one previous unsuccessful IVF treatment cycle (mean 2.4). Intervention(s): This study used a novel chromosome screening approach, combining biopsy of several trophectoderm cells on day 5 after fertilization and detailed analysis of all 24 types of chromosome using comparative genomic hybridization. Main Outcome Measure(s): Proportion of embryos yielding a diagnostic result, aneuploidy rate, implantation rate, and pregnancy rate. Result(s): A diagnosis was obtained from 93.7% of embryos tested. The aneuploidy rate was 51.3%. The probability of an individual transferred embryo forming a pregnancy reaching the third trimester/birth was 68.9%, an implantation rate 50% higher than contemporary cycles from the same clinic. The pregnancy rate was 82.2%. Conclusion(s): The comprehensive chromosome screening method described overcomes many of the problems that limited earlier aneuploidy screening techniques and may finally allow preimplantation genetic screening to achieve the benefits predicted by theory. The high embryo implantation rate achieved is particularly encouraging and, if confirmed in subsequent studies, will be of great significance for IVF clinics attempting to reduce the number of embryos transferred or to implement single embryo transfer. ©2010 by American Society for Reproductive Medicine.